Hamlin Garland papers - Garland, Hamlin, 1860-1940.
TLS (1904 December 1) written to Charles Warren Stoddard by Garland as chairman of a committee sponsoring a dinner commemorating the twenty-fifth anniversary of the publication of Henry George's Progress and Poverty (1879), ALS ([1925] 28 December) from Garland thanking Ms. Cole (Alice Cole Scheips) for her letter, and ALS (1940 January 20) written by Garland to a Mr. Thompson thanking him for his letter and poems. Includes an undated scrapbook page compiled by Scheips concerning Garland and other authors.
Author and dramatist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: George, Henry, -- 1839-1897.; Scheips, Alice Cole -- Correspondence; Stoddard, Charles Warren, -- 1843-1909 -- Correspondence; Thompson, -- Mr. -- Correspondence; Authors; Dramatists